Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1111/j.1365-2729.2007.00259.x
|View full text |Cite
|
Sign up to set email alerts
|

Fostering elementary school students’ understanding of simple electricity by combining simulation and laboratory activities

Abstract: Computer simulations and laboratory activities have been traditionally treated as substitute or competing methods in science teaching. The aim of this experimental study was to investigate if it would be more beneficial to combine simulation and laboratory activities than to use them separately in teaching the concepts of simple electricity. Based on their pre-test performances, 66 elementary school students were placed into three different learning environments: computer simulation, laboratory exercise and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

13
115
1
19

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(148 citation statements)
references
References 40 publications
13
115
1
19
Order By: Relevance
“…Olympiou and Zacharia (2011) documented positive effects and showed that a combination of lab experiments and virtual tools enhanced students' conceptual understanding of light and colour more than the use of lab experiments or virtual tools alone. Jaakkola and Nurmi (2008) noted similar findings in a study focusing on elementary students' understanding of current circuits in a setting that combined lab experiment and a simulation. A study undertaken by Kozma (2003) involving analyses of peer group dialogues when engaging with digital representations of chemical reactions gave some indication of why such digital representations constitute productive learning resources in CSCL settings.…”
supporting
confidence: 48%
“…Olympiou and Zacharia (2011) documented positive effects and showed that a combination of lab experiments and virtual tools enhanced students' conceptual understanding of light and colour more than the use of lab experiments or virtual tools alone. Jaakkola and Nurmi (2008) noted similar findings in a study focusing on elementary students' understanding of current circuits in a setting that combined lab experiment and a simulation. A study undertaken by Kozma (2003) involving analyses of peer group dialogues when engaging with digital representations of chemical reactions gave some indication of why such digital representations constitute productive learning resources in CSCL settings.…”
supporting
confidence: 48%
“…The popularity of simulation environments such as PhET (Perkins et al 2006) has led policy-makers and scholars to question the real value of physical laboratories-especially in the face of the associated costs and logistics. A wave of research studies within the past 10 years has explored: (a) What are the advantages of physical laboratories relative to virtual laboratories and manipulatives, (b) whether the latter can replace the former (Triona and Klahr 2003), and (c) in what ways virtual models can simulate complex phenomena and permit student experimentation in domains that might otherwise be costly, impractical, or dangerous (Finkelstein et al 2005;Jaakkola and Nurmi 2008;Jaakkola et al 2011;Klahr et al 2007; Perkins et al 2006;Resnick and Wilensky 1998).The literature comparing hands-on or physical models (PM) with virtual models (VM) for science learning has sought to establish rules for choosing one modality over the other or for ordering them as distinct phases in a sequential process (de Jong et al 2013). Zacharia and Anderson (2003) found that combining physical and virtual models increased teachers' learning of content knowledge in physics.…”
mentioning
confidence: 99%
“…Thus, it is particularly emphasized that some even more effective virtual laboratory environments could be formed in accordance with the specific needs of the users. Whenever the presently available studies are examined properly, it is suggested in the researches to use the virtual laboratory programs in ensuring the appropriate application environment for the students before the real physics laboratory applications [9,13,15,19,20].…”
Section: Resultsmentioning
confidence: 99%
“…Preparation for the real laboratory tests and experiments and providing support and assistance [11,13,14,15,16]. 2.…”
Section: Resultsmentioning
confidence: 99%